2010
DOI: 10.4141/cjps08192
|View full text |Cite
|
Sign up to set email alerts
|

Diversity comparison and phylogenetic relationships of cocksfoot (Dactylis glomerata L.) germplasm as revealed by SSR markers

Abstract: . 2010. Diversity comparison and phylogenetic relationships of cocksfoot (Dactylis glomerata L.) germplasm as revealed by SSR markers. Can. J. Plant Sci. 90: 13Á21. Phylogenetic relationships among and within 16 accessions collected from China, Russia, Kazakhstan, India and Japan were investigated using SSR markers. The 21 SSR primer pairs generated a total of 143 polymorphic alleles, with an average of 6.8 alleles per locus, and a range of 3Á13 alleles. The average genetic diversity, as measured by the polymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 40 publications
1
15
1
Order By: Relevance
“…The results indicated that all 3 locations had relatively high level of genetic variation for polymorphic rates (P = 100%) based on both SSR and ISSR markers. Polymorphism in the present study was higher compared to previous reports on SSR variation (P = 84.63) (Xie et al, 2010), ISSR variation (P = 86.3) (Xie et al, 2010), and AFLP variation (P = 84%) (Peng et al, 2008).…”
Section: Molecular Analysiscontrasting
confidence: 55%
See 2 more Smart Citations
“…The results indicated that all 3 locations had relatively high level of genetic variation for polymorphic rates (P = 100%) based on both SSR and ISSR markers. Polymorphism in the present study was higher compared to previous reports on SSR variation (P = 84.63) (Xie et al, 2010), ISSR variation (P = 86.3) (Xie et al, 2010), and AFLP variation (P = 84%) (Peng et al, 2008).…”
Section: Molecular Analysiscontrasting
confidence: 55%
“…Genetic variability mainly existed within rather than among the tested locations, as shown by AMOVA, based on both SSRs and ISSRs. Similarly, analysis of molecular variation (AMOVA) based on SSRs revealed larger genetic variation within accessions (65.75%) and geographical regions (75.58%), rather than between them, in the analysis of 16 D. glomerata accessions collected from China, Russia, Kazakhstan, India, and Japan (Xie et al, 2010). In addition, Kölliker et al (1999) obtained 85% variability within 3 cultivars of D. glomerata.…”
Section: Molecular Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Heterologous marker transferability also decreases as species diverge (Thiel et al 2003;Zhang et al 2005;Litrico et al 2009), and are accompanied by higher likelihood of homoplasy and polymorphism due to mutations that exist among the species (Thiel et al 2003;Saha et al 2004;Zhang et al 2006). Recently, genomic library-derived SSR markers were used to describe relationships among some Asian germplasm (Xie et al 2010). Genomic SSR markers also tend to have lower transferability and amplification success than EST-derived SSR markers across diverse germplasm (Varshney et al 2005;Xie et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, genomic library-derived SSR markers were used to describe relationships among some Asian germplasm (Xie et al 2010). Genomic SSR markers also tend to have lower transferability and amplification success than EST-derived SSR markers across diverse germplasm (Varshney et al 2005;Xie et al 2010). In contrast to these approaches, EST-derived markers developed from within a target species can circumvent these constraints and provide sufficient polymorphism.…”
Section: Introductionmentioning
confidence: 99%